Oral combined contraceptives induce liver mitochondrial reactive oxygen species and whole‐body metabolic adaptations in female mice. (2nd December 2022) - Fuller, Kelly N. Z.; McCoin, Colin S.; Stierwalt, Harrison; Allen, Julie; Gandhi, Shivam; Perry, Christopher G. R.; Jambal, Purevsuren; Shankar, Kartik; Thyfault, John P.
Abstract : Abstract: Compared to age‐matched men, pre‐menopausal women show greater resilience against cardiovascular disease (CVD), hepatic steatosis, diabetes and obesity – findings that are widely attributed to oestrogen. However, meta‐analysis data suggest that current use of oral combined contraceptives (OC) is a risk factor for myocardial infarction, and OC use further compounds with metabolic disease risk factors to increase CVD susceptibility. While mitochondrial function in tissues such as the liver and skeletal muscle is an emerging mechanism by which oestrogen may confer its protection, effects of OC use on mitochondria and metabolism in the context of disease risk remain unexplored. To answer this question, female C57Bl/6J mice were fed a high fat diet and treated with vehicle or OCs for 3, 12 or 20 weeks ( n = 6 to 12 per group) at a dose and ratio that mimic the human condition of cycle cessation in the low oestrogen, high progesterone stage. Liver and skeletal muscle mitochondrial function (respiratory capacity, H2 O2, coupling) was measured along with clinical outcomes of cardiometabolic disease such as obesity, glucose tolerance, hepatic steatosis and aortic atherosclerosis. The main findings indicate that regardless of treatment duration, OCs robustly increase hepatic mitochondrial H2 O2 levels, likely due to diminished antioxidant capacity, but have no impact on muscle mitochondrial H2 O2 . Furthermore, OC‐treated mice had lower adiposity and hepatic triglyceride content compared to control mice despite reduced wheel running, spontaneous physical activity and total energy expenditure. Together, these studies describe tissue‐specific effects of OC use on mitochondria as well as variable impacts on markers of metabolic disease susceptibility. Key points: Oestrogen loss in women increases risk for cardiometabolic diseases, a link that has been partially attributed to negative impacts on mitochondria and energy metabolism. To study the effect of oral combined contraceptives (OCs) on hepatic and skeletal muscle mitochondria and whole‐body energy metabolism, we used an animal model of OCs which mimics the human condition of cessation of hormonal cycling in the low oestrogen, high progesterone state. OC‐treated mice have increased hepatic mitochondrial oxidative stress and decreased physical activity and energy expenditure, despite displaying lower adiposity and liver fat at this time point. These pre‐clinical data reveal tissue‐specific effects of OCs that likely underlie the clinical findings of increased cardiometabolic disease in women who use OCs compared to non‐users, when matched for obesity. Abstract : Abstract figure legend Oral contraceptive treatment in female mice decreases physical activity and energy expenditure and increases hepatic mitochondrial oxidative stress without negatively impacting glucose tolerance.